ANALISIS TINGKAT KEPUASAN PASIEN PESERTA BPJS TERHADAP PELAYANAN KESEHATAN DI PUSKESMAS - Wotok, Nobertus Wuli; Asiah, Nur; Nordianiwati, Nordianiwati; Putra, Ryryn Suryaman Prana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Community health centers play an important role in the national health system, particularly in the provision of primary health care. Patient dissatisfaction with health care is an issue that often arises in various experiences and observations. The purpose of this study was to analyze the level of satisfaction of BPJS participants with health care at community health centers. A cross-sectional study design was used in this study. The study was conducted at the Sudiang Raya Community Health Center. The research was conducted in August 2024. The population consisted of all BPJS patients who received health services at the Sudiang Raya Community Health Center in the city. The sample consisted of 94 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between responsiveness (p value: 0.015) and empathy (p value: 0.039) and the satisfaction of BPJS Kesehatan patients. It is recommended that the Community Health Center make improvements, particularly regarding responsiveness and empathy, by providing training in communication skills to health workers so that the information provided can be accepted and easily understood by patients and their families, as well as providing fairness to every customer and understanding customer needs. Keywords: BPJS, Empathy, Responsiveness, Community Health Center